Robles, Gonzalo. Ensayos sobre el desarrollo de México. México : Banco de México, S.A : Fondo de Cultura Económica, 1982. 409 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1983)
ROBLES, GONZALO, Ensayos sobre el desarrollo de México, Banco de México, S. A.; Fondo de Cultura Económica, 1982.